Ciri Intrinsik Novel Populer Indonesia yang Terbit Tahun 1980-An - Redyanto Noor (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
Since the growth of the Indonesian press industry in the 1970s, popular novels have been carried away by the rapid development of the mass media world. Because, there are facts and data that most of Indonesia's popular novels were originally published as serials in newspapers and magazines. Convincingly people can classify certain novels into groups of literary novels or popular novels. The reasons that are subjective are not appropriate to be used as a criterion for determining certain novels as serious (literary) novels or popular novels, because the considerations used are only based on personal perception. Of course it is scientifically less accountable, because it is not based on clear theories and methods, for example by looking at intrinsic and extrinsic structures, or also its sociological aspects. Therefore, an inventory of the intrinsic features of popular novels is very important. These characteristics include romantic-sentimental, love and household themes, single channel, straight channeling, contemporary dialogue, physical background of a rich family environment, educated family, campus, spectacular and explosive disposition, anti-double meaning, no need for aesthetic understanding .